Differential Expansion of Zinc-Finger Transcription Factor Loci in Homologous Human and Mouse Gene Clusters - Shannon, Mark; Hamilton, Aaron T.; Gordon, Laurie; Branscomb, Elbert; Stubbs, Lisa

(untitled) (Genome Research, 2003)
Mammalian genomes carry hundreds of Krüppel-type zinc finger (ZNF) genes, most of which reside in familial clusters. ZNF genes encoding Krüppel-associated box (KRAB) motifs are especially prone to this type of tandem organization. Despite their prevalence, little is known about the functions or evolutionary histories of these clustered gene families. Here we describe a homologous pair of human and mouse KRAB-ZNF gene clusters containing 21 human and 10 mouse genes, respectively. Evolutionary analysis uncovered only three pairs of putative orthologs and two cases where a single gene in one species is related to multiple genes in the other; several human genes have no obvious homolog in mouse. We deduce that duplication and loss of ancestral cluster members occurred independently in the primate and rodent lineages after divergence, yielding substantially different ZNF gene repertoires in humans and mice. Differences in expression patterns and sequence divergence within the DNA binding regions of predicted proteins suggest that the duplicated genes have acquired novel functions over evolutionary time. Since KRAB-ZNF proteins are predicted to function as transcriptional regulators, the elaboration of new lineage-specific genes in this and other clustered ZNF families is likely to have had a significant impact on species-specific aspects of biology.